Factors Influencing Misinformation Propagation: A Systemic Review - HAN Xi, LIAO Ke (Nongye tushu qingbao xuebao)
[Purpose/Significance] The spread of misinformation on social media has caused serious harm and attracted attention from various disciplines. This study aims to systematically examine the factors associated with the propagation of misinformation. It contributes to the existing literature by providing an integrated model of the factors influencing misinformation propagation, which is crucial for understanding and mitigating the spread of misinformation. [Method/Process] The search strategy, developed with the help of librarians, was searched in six Chinese and foreign databases. Four researchers coded the information back-to-back to ensure the accuracy of the analysis. Our literature screening criteria were rigorous to ensure that only high quality and relevant research was included. A total of 108 empirical studies related to misinformation propagation were included. The factors were summarized and sorted from multiple perspectives such as disciplinary field, theoretical foundation, research methods and different roles. [Results/Conclusions] Research on this topic has grown rapidly in recent years. Scholars from a variety of disciplines have used survey and experimental methods to study misinformation in the areas of politics and health. Pedictors of misinformation propagation are mainly studed from the perspective of users and information, including objective characteristics of information, perceptual characteristics of information, as well as individual characteristics, cognitive characteristics, and perceptual characteristics of users. The results show that individual characteristics play a critical role in shaping users' intention and behavior to propagate misinformation. Individual characteristics are the most frequently studied factors, while information and situational characteristics have received less attention. Psychological and behavioral variables, including users' cognitive, emotional, and behavioral responses play key mediating roles in this process. In addition, the types of information, individual attributes, cognitive characteristics, social interactions, personal knowledge, behavior and emotions play moderating roles. This study constructs an integrated model of the influencing factors for misinformation propagation, which can provide direction for targeted interventions and algorithm design to mitigate the spread of misinformation. The study also identified some limitations of current studies, including an excessive focus on the political and health issues, a lack of attention to how information characteristics, intervention factors, and platform characteristics play a role, and the relative simplicity of the research methods. Future studies should focus on misinformation propagation in other scenarios, explore more information characteristics suitable for algorithmic intervention, examine the differences in misinformation propagation on different platforms, and use mixed research methods to reach more credible conclusions. This study provides directions and goals for multi-agent collaborative misinformation management.